2013
DOI: 10.5402/2013/180439
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Kato-Katz, Wet Mount, and Formol-Ether Concentration Diagnostic Techniques for Intestinal Helminth Infections in Ethiopia

Abstract: Objective. The aim of this study was to evaluate the operational characteristics (sensitivity and negative predictive value (NPV)) of wet mount, formol-ether concentration (FEC), and Kato-Katz techniques for the determination of intestinal parasitic infections. Method. A total of 354 faecal specimens were collected from students in Northwest Ethiopia and screened with Kato-Katz, wet mount, and FEC for the presence of intestinal parasitic infection. Since a gold standard test is not available for detection of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

20
32
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 15 publications
20
32
4
Order By: Relevance
“…Moreover, the presence of large stool debris materials in the DWMM may conceal the parasitic ova. The sensitivity of DWMM in this study (37%) is similar with other studies done in Ethiopia (25,27). This suggests that DWMM has resulted in around 63% false negative reports during hookworm diagnosis.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Moreover, the presence of large stool debris materials in the DWMM may conceal the parasitic ova. The sensitivity of DWMM in this study (37%) is similar with other studies done in Ethiopia (25,27). This suggests that DWMM has resulted in around 63% false negative reports during hookworm diagnosis.…”
Section: Discussionsupporting
confidence: 89%
“…The speci city of all of the stool examination methods described in this study was 100%, and this is in line with ndings of a study done in Gondar which revealed that DWMM, FEC and KK had greater than 97% of sensitivity (27). The current study also analyzed the level of agreement of the various types of hookworm diagnosis methods with composite reference standard.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, the result of the present study is in contrary to previous studies done in Peusangan Bireuen [33] and Ethiopia [34,35]. These differences in diagnostic performance might be due to stool sample size, number of slides prepared for diagnosis, inter personal skill variations and technical errors of the two methods.…”
Section: Discussioncontrasting
confidence: 99%
“…Contradictory results have been reported in the literature on the effectiveness of Kato-Katz and Formolether techniques in the detection of gastrointestinal parasites in faeces. Some authors have noted that the Kato-Katz technique was better and significantly more sensitive than the other method (18)(19) while others have reported that the Formol-ether technique had a better sensitivity than the Kato-Katz method (20)(21). According to Knight et al, (22), the concentration of eggs in the faeces enabled the detection of more patients infected with S. mansoni when the Formol-ether technique was used.…”
Section: Discussionmentioning
confidence: 99%